Shear strength of fibre reinforced clay soil - Wong , Pei Yin (2012)
Improving the soil condition in order to provide a greater advantage in supporting the structure above ground has always been the major interest for geotechnical engineer or specialist. An effective improvement method can guarantee a greater development potential for the country and hence bring numerous benefits to the nation people. Among all the types of soil existing on our country's ground, clayey soil is one of them. Unfortunately, clay soil is known to have low supporting strength compared to others type of soil in the construction industry. Hence, this project is to investigate the shear strength behaviour of medium plasticity clayey soil responding on the influential of fibre percentage. The fibre was prepared by cutting the fishing threads into 1-2mm in length and the soil sample was collected around UMP. A range of fibres percentages were added corresponding with the soil mass in a random distribution manner and the shear strength parameters were determined using unconsolidated undrained triaxial compression test method. The result proved that the fibre reinforced clayey soil has a relatively higher shear strength compared with the unreinforced clayey soil. The increment of shear strength is proved to be 49% for the fibre percentage of 0.4 which is the optimum fibre content percentage where it gives the highest increment of shear strength. Anyhow, the increment percentage is relatively low compared with the published data of similar research.